Stabilitas Hasil Tiga Klon Kopi Robusta Bengkulu sebagai Klon Unggul Lokal - Enny Randriani; Edi Wardiana (Jurnal Tanaman Industri dan Penyegar, 2015)
The population of Robusta coffee in Bengkulu province were mostly old thus it need rejuvenation or rehabilitation.  Local clones of Robusta coffee, such as Sidodadi, Payung Hijau and Payung Kuning, have been cultivated for rehabilitation in Bengkulu Province at an altitude of >700 m above sea level (asl). This study aimed to analyze the yield stability of the three Robusta coffee clones at medium to high altitudes. The study was conducted from January to September 2015 in Curup Regency (670 m asl) and Kepahiang Regency (900 m and 1300 m asl), Bengkulu Province. The three tested Robusta coffee clones were 5 years old Sidodadi, Payung Hijau, and Payung Kuning,which propagated through plagiotropic grafting. Each experiment unit consisted of 5 plant samples and were obtained by randomized sampling with 5 replications respectively. The parameters observed were fresh weight of berry/plant, dry weight of beans/plant, fresh weight/berry, and dry weight/beans. The data analyzed using combined variance followed by yield stability test of Eberhart and Russell method. The results showed that Payung Hijau clone had the highest bean yield compared to the other two clones (Sidodadi and Payung kuning). The production of Payung Hijau clone reached 1.19 kg dry weight of bean/plant, 4.31 g fresh weight/berry, and 0.63 g dry weight/bean. Therefore, the Payung Hijau clone was potentially used as scions source for the coffee plantation rejuvenation or rehabilitation.